Plant genetic resources conservation and management - Paroda, R.S.; Arora, R.K.; International Board for Plant Genetic Resources (1991)
This book, the first of its kind in the Indian context, will be found useful by researchers/users and curators engaged in plant genetic resources activities, by the teachers and post-graduate students in traditional and State Universities and equally so, by the policy-makers and conservationists advocating national concern on plant genetic conservation and management. It will also be of use to the PGR community within the region of South and Southeast Asia. Available from IPGRI Office for South Asia.